Difficulties of Integrating Human Resources Management Globally by Japanese Corporations - Takakuwa, Kentaro (International Journal for Applied Information Management, 2021)
International enterprises should integrate human resource management globally under a multi-dimensional global market. But the globalized level of Japanese companies’ human resource management has been low for decades. This might have structural causes, then they couldn't execute necessary policy change. I found this structural problem which prevents Japanese companies from offering attractive job opportunities to foreign workers through international comparison of the relation between labor market and incentive system to attitudes of work. The experienced labor market is imperfect only in Japan. This situation enhances the accumulation of “context-oriented human assets”. Seniority based rewards systems promote them to co-operate then increase the performance of this kind of human asset. In contrast, “independent human asset” would be accumulated in other countries, such as South Korea, China, Indonesia, United States and Brazil, except Germany. The experienced labor market is relatively perfect in these countries, and those who put priority on both good rewards and clear career path when seeking job opportunities get good rewards. Because this kind of incentive system seen in the countries except Japan and Germany have inconsistency with that is seen in Japanese homeland office, Japanese companies couldn’t integrate human resource management globally. Japanese companies need a fundamental change of organizational architecture to regain the international competitiveness and utilize the new market opportunity overseas.